Interleukin-15 and cancer: some solved and many unsolved questions. Issue 2 (17th November 2020) - Fiore, Piera Filomena; Di Matteo, Sabina; Tumino, Nicola; Mariotti, Francesca Romana; Pietra, Gabriella; Ottonello, Selene; Negrini, Simone; Bottazzi, Barbara; Moretta, Lorenzo; Mortier, Erwan; Azzarone, Bruno
Abstract : Soluble interleukin (IL)-15 exists under two forms: as monomer (sIL-15) or as heterodimeric complex in association with sIL-15Rα (sIL-15/IL-15Rα). Both forms have been successfully tested in experimental tumor murine models and are currently undergoing investigation in phase I/II clinical trials. Despite more than 20 years research on IL-15, some controversial issues remain to be addressed. A first point concerns the detection of the sIL-15/IL-15Rα in plasma of healthy donors or patients with cancer and its biological significance. The second and third unsolved question regards the protumorigenic role of the IL-15/IL-15Rα complex in human cancer and the detrimental immunological consequences associated to prolonged exposure of natural killer (NK) cells to both forms of soluble IL-15, respectively. Data suggest that in vivo prolonged or repeated exposure to monomeric sIL-15 or the soluble complex may lead to NK hypo-responsiveness through the expansion of the CD8 + /CD44 + T cell subset that would suppress NK cell functions. In vitro experiments indicate that soluble complex and monomeric IL-15 may cause NK hyporesponsiveness through a direct effect caused by their prolonged stimulation, suggesting that this mechanism could also be effective in vivo. Therefore, a better knowledge of IL-15 and a more appropriate use of both its soluble forms, in terms of concentrations and time of exposure, are essential in order to improve their therapeutic use. In cancer, the overproduction of sIL-15/IL-15Rα could represent a novel mechanism of immune escape. The soluble complex may act as a decoy cytokine unable to efficiently foster NK cells, or could induce NK hyporesponsiveness through an excessive and prolonged stimulation depending on the type of IL-15Rα isoforms associated. All these unsolved questions are not merely limited to the knowledge of IL-15 pathophysiology, but are crucial also for the therapeutic use of this cytokine. Therefore, in this review, we will discuss key unanswered issues on the heterogeneity and biological significance of IL-15 isoforms, analyzing both their cancer-related biological functions and their therapeutic implications.